THE NATURE OF IRREDENTISM: THEORETICAL ASPECT - Рябінін, Є.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In this article such a pressing problem as irredentism is considered. The views of some experts are taken into account that irredentism is a problem of the past, besides the author’s viewpoint is presented as for the reasons of such a movement increase. It is stressed that there could be not only domestic, but also outside factors that may work as a catalyst for irredentism movement and nationalism is a fundamental for these processes. Besides, it is underlined that identity will play a certain role in geopolitical processes in the XXI century.